1982
DOI: 10.1126/science.6753152
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Solution of Water in Organic Solvents: a Microheterogeneous Medium for Enzymatic Reactions

Abstract: To simulate in vitro the conditions under which enzymes act in vivo, enzyme molecules have been entrapped in hydrated reverse micelles of a surfactant in organic solvents. In this system the catalytic activity of one of the enzymes studied (peroxidase) became much higher than in water, and the specificity of the other enzyme (alcohol dehydrogenase) was dramatically altered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0
2

Year Published

1985
1985
2010
2010

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 200 publications
(74 citation statements)
references
References 25 publications
1
71
0
2
Order By: Relevance
“…H # O # and n-octane were purchased from Reakhim (Moscow, Russia). The latter was purified as described in [20]. H # O # concentration was determined spectrophotometri- cally, using a molar absorption coefficient of 72.7 M −" :cm −" at 230 nm [21].…”
Section: Experimental Materialsmentioning
confidence: 99%
“…H # O # and n-octane were purchased from Reakhim (Moscow, Russia). The latter was purified as described in [20]. H # O # concentration was determined spectrophotometri- cally, using a molar absorption coefficient of 72.7 M −" :cm −" at 230 nm [21].…”
Section: Experimental Materialsmentioning
confidence: 99%
“…It is seen that the kinetic parameters, particularly the values of the Michaelis constant, observed in aqueous solution differ considerably from those determined in the micellar system. This difference results in a profound change in the observed substrate specificity of HLADH on going from aqueous solution to the system of hydrated reversed AOT micelles in octane [13,14]. The dependence of the second-order rate constant, kc,,/&,, which is the measure of the substrate specificity of the enzyme, on the hydrocarbon chain length of alcohols is shown in Fig.…”
Section: Application Of the Model For Description Ojthe Kinetic Behavmentioning
confidence: 99%
“…The length of the initial linear part of kinetic curves depended on the nature of alcohol and usually was of the order of several minutes, which was sufficient for the reliable determination of the initial slope. A more detailed description of the kinetic studies of HLADH in AOT reversed micelles can be found in previous publications [13,141.…”
Section: Kinetic Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Meier and Luisi [I 61 have studied the kinetics of acetaldehyde reduction in Aerosol-OT microemulsion. Martinek et al [17,181 investigated the equilibrium constants and substrate specificity for oxidation of alcohols. Lee and Biellman [19,201 have studied kinetics for NAD and storage stability in Triton X-100, SDS and cetyhimethyhmmonium bromide microemulsions.…”
mentioning
confidence: 99%